Excitation-mode-selective emission through multiexcitonic states in a double perovskite single crystal - Hao Suo; Nan Wang; Yu Zhang; Xin Zhang; Jinmeng Xiang; Xiaojia Wang; Guansheng Xing; Dongxu Guo; Jiwen Chang; Yu Wang; Panlai Li; Zhijun Wang; et al. (Light: Science & Applications)
Abstract Low-dimensional lead-free metal halide perovskites are highly attractive for cutting-edge optoelectronic applications. Herein, we report a class of scandium-based double perovskite crystals comprising antimony dopants that can generate multiexcitonic emissions in the ultraviolet, blue, and yellow spectral regions. Owing to the zero-dimensional nature of the crystal lattice that minimizes energy crosstalk, different excitonic states in the crystals can be selectively excited by ultraviolet light, X-ray irradiation, and mechanical action, enabling dynamic control of steady/transient-state spectral features by modulating the excitation modes. Remarkably, the transparent crystal exhibits highly efficient white photoluminescence (quantum yield >97%), X-ray excited blue emission with long afterglow (duration >9 h), and high-brightness self-reproducible violet-blue mechanoluminescence. These findings reveal the exceptional capability of low-dimensional perovskite crystals for integrating various excitonic luminescence, offering exciting opportunities for multi-level data encryption and all-in-one authentication technologies.